2000
DOI: 10.1046/j.1365-2516.2000.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human parvovirus B19 and TT virus in a group of young Haemophiliacs in South Africa

Abstract: A well recognized hazard of transfusion with blood or blood products is the acquisition of a viral infection. Parvovirus B19 and transfusion transmitted virus (TTV) are two of several non-enveloped viruses that may on rare occasions be present in coagulation factor concentrates. The prevalence of these viruses in the South African Haemophilia population has not previously been studied. Thirty-nine Haemophiliac children were investigated for evidence of parvovirus and TTV infection. 26 boys with Haemophilia A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The result of the present study showed 12.8% prevalence of B19V DNA and 9.3% of PARV4 DNA. A similar work in South Africa revealed an 8% prevalence of B19V infection among 26 patients with hemophilia [ 8 ], which is a lower rate than that of the current study; however, the sample size in the South African study was very small. Slavov in Brazil demonstrated that active infection of B19V was as high as 35.7% among 28 patients [ 25 ].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The result of the present study showed 12.8% prevalence of B19V DNA and 9.3% of PARV4 DNA. A similar work in South Africa revealed an 8% prevalence of B19V infection among 26 patients with hemophilia [ 8 ], which is a lower rate than that of the current study; however, the sample size in the South African study was very small. Slavov in Brazil demonstrated that active infection of B19V was as high as 35.7% among 28 patients [ 25 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Although the use of coagulation factors can lead to improved morbidity and survival in patients with hemophilia, there is still a risk of B19V infection by continuous administration of plasma-derived factors [ 7 ]. Common inactivation procedures remove enveloped viruses but do not appear to effect B19V owing to its characteristics of greater resistance to physicochemical agents and having such a small non-enveloped capsid [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 1997 TTV was defined as a virus causing hepatitis related to transfusion and was found to be responsible for 25-45% of the fulminant or chronic hepatitis of unknown origin [1-3, 8, 12]. The prevalence of TTV was also reported to be 69-94% in thalassemic patients on chronic transfusion regimes, 24-78% in hemophilic patients, and 2-60% in blood donors [1,[13][14][15][16][17]. TTV DNA was previously detected in Turkey in 14% of children with chronic liver diseases, 61% of adult thalassemia patients, and 52% of blood donors [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated B19V PCR positivity rates in haemophilic patients from Brazil were higher compared to other countries like Germany (5·8%) (Grosse-Bley et al, 1994), the USA (0·7%) (Ragni et al, 1996) and the Republic of South Africa (Cape Town, 5·1%) (Rubinstein et al, 2000), despite the smaller number of patients tested. The described B19V DNA prevalence in healthy Brazilian blood donors (general population) is up to 1% (Slavov et al, 2012), and therefore, our results do not exclude a higher occurrence of B19V in patients with haemophilia.…”
Section: Dear Sirmentioning
confidence: 73%